APPLICATION OF IMMUNOAFFINITY CHROMATOGRAPHY FOR PURIFICATION OF ANTIBODY AGAINST DOMOIC ACID PRODUCED IN NEW ZEALAND WHITE RABBIT’S SERUM - Ha, Dao Viet; Ky, Pham Xuan (Vietnam Journal of Marine Science and Technology, 2017)
In order to develop an ELISA KIT for detection of domoic acid (DA) in seafood in Vietnam, DA antibody was produced by immunizing in New Zealand white rabbit using DA-DSS (disuccinimidyl suberate)-BSA (Bovine Serum Albumin) as an antigen. The DA antibody in rabbit’s serum was purified for its use as a material of ELISA KIT. In antibody/antigen purification process, immunoaffinity chromatography (IAC) is considered as the best method by both its specification and ability to enrich antibody. However, DA is a hapten, and it is impossible to apply a regular immunizing principal for making an IAC column with DA as a solid phase to catch DA antibody. This paper presents a trial using polymer sepharose EAH 4B resin (omega-aminohexyl) IAC bound with hapten DA as a solid phase for DA antibody purification from rabbit’s serum. Using DSS as a chemical linker; then, based on the reaction between a carboxyl group of DA and a carbodiimide group of the resin EAH 4B, we were successful to make the IAC column with DA-DSS as the solid phase. Recovery ratio of the made IAC column reached 91.5 ± 1.5% (n = 3) to capture the antibody against DA standard. DA antibody from white rabbit’s serum was eluted successfully using this column with 0.5 M NaCl; 0.1 M PBS and then, 0.1 M Ldy-HCl solutions (pH 2.7). The obtained antibody was qualified by Western Blot using a specific reaction with the 2nd specific antibody HRP-labeled anti-goat IgG and the confirmed result revealed that it can be used as ELISA KIT material.